Bagaimana jika Standar Kecantikan tidak ada? - Anisa Alfikriyah; Arya Guna Suwandi (Motivaksi: Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
In the article entitled What if Beauty Standards doesn’t exist, it discusses Beauty standards in Indonesia and their impact on individuals and society. Beauty standards are a fluid social concept, reflecting society's views on what is considered ideal physical appearance. Beauty standards are subjective, there is pressure in the form of social pressure to meet these beauty standards and is often strong and can have negative impacts, such as using dangerous substances or feeling insecure. It is important to change the paradigm about beauty by accepting and liking yourself, and appreciating diversity. Individuals can live life happier and more confident in their own skin.